Verbal etiquette as a part of Russian language picture of the world (the word-formation approach) - HARUTYUNYAN, VERONIKA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the category of verbal etiquette in Russian language. Characteristics of linguistic expression of this category, particularly at the word-formative level, prove, that it is a part of national language picture of the world, it is the way to express the main national keу ideas.